Kompetensi Pedagogik Guru Dan Motivasi Siswa Terhadap Kreatifitas Siswa Mata Pelajaran Ekonomi Kelas X SMA Negeri 1 Ngemplak Boyolali Tahun Ajaran 2015/2016 - Yonanda Dewati, Ayunita; , Drs. Sabar Narimo, MM.M.Pd (2016)
The purpose of this study is: 1) To determine the influence of pedagogical competence of the students' creativity . 2 ) To determine the influence of students 'motivation to learn students' creativity . 3 ) To determine the influence of pedagogical competence of teachers and students 'motivation to learn students' creativity SMAN 1 Boyolali Ngemplak Academic Year 2015/2016 . This research is quantitative research with the associative drawing conclusions through statistical methods. The population in this study were all students of class X SMA Negeri 1 Ngemplak Boyolali academic year 2015/2016. Samples taken as many as are 161 students with proportional and insindental sampling. Necessary data obtained through questionnaires and observation . The questionnaire previously tested and tested for validity and reliability were tested . Data analysis technique used is multiple linear regression analysis , t-test, F , and the relative contribution and effective. The results of the regression analysis obtained regression equation : Y = 6,109 + 0, 462 X1 + 0, 396 X2.. The equation shows that the creativity of student learning is influenced by pedagogical and students' motivation . The conclusions drawn were: 1 ) " There is the influence of pedagogical competence for the creativity of student learning " is acceptable . This is based on multiple linear regression analysis ( t test ) note that tcount > ttable , namely 5.775 > 1.960 and the significance value < 0.05 , ie 0,000 effective contribution of 25.3 % .2 )" There is the influence students 'motivation to learn students' creativity" acceptable. This is based on multiple linear regression analysis ( t test ) note that tcount > ttable , namely 5.309 > 1.960 and the significance value < 0.05 , ie 0,000 effective contribution of 23.3 % .3 )" There is the influence of pedagogical and students 'motivation to learn students' creativity" is acceptable. This is based on multiple linear regression analysis of variance ( F test ) is known that F count > F table , ie 20.325 > 3.000 and the significance value < 0.05 , ie 0,000.4 ) The result of the coefficient of determination (R2 ) of 0.486 indicates that the influence of pedagogical competence and motivation of students learning together for the creativity of student learning is by 48.6 % , while 51.4 % is influenced by other variables not examined